Building Resilience to Chronic Landslide Hazard Through Citizen Science - Cieslik, Katarzyna; Shakya, Puja; Uprety, Madhab; Dewulf, Art; Russell, Caroline; Clark, Julian; Dhital, Megh Raj; Dhakal, Amrit (Frontiers in Earth Science, 2019)
Landslides disrupt livelihoods, cause loss of human lives and damages to property and infrastructure. In the case of Nepal, the destructive impact of landslides has been steadily increasing as a result of the rising occupation of marginal land and extreme weather events caused by climate change. In particular, the impacts of seasonal, shallow landslides have been underestimated due to underreporting, and lack appropriate policy response. Within this paper, we argue that citizen science – the practice of incorporating the general public in the process of knowledge co-production – may help address this issue by increasing the knowledge base of stakeholders at different levels. We present the preliminary results from an interdisciplinary scoping study of two landslide sites in Western Nepal, in Bajhang and Bajura, where the Landslide-EVO research project, including a citizen science component, is currently being implemented. The aim of the project is to innovate participatory environmental monitoring and to generate evidence to support resilience. Our exploratory qualitative investigation outlines the strategies currently employed by the local communities that continue living in the landslide affected areas. These include demographic shifts and patterns, land use changes and occupational diversification. We argue that these existing local adaptation and mitigation practices compound a wealth of experiential knowledge. Based on evidence from literature, as well as our first-hand experience of starting citizen science activities in the both landslide sites, we argue that citizen science has the potential to build on local knowledge base and strengthen the adaptive capacities of different level stakeholders. Our theoretical contribution is the proposed typology of citizen-science interventions. We distinguish between community science, participatory environmental monitoring and virtual citizen science, providing examples of how they can benefit stakeholders at different levels and/or different types of research. Finally, we examine the ways in which different types of citizen science could be applied in our case study sites, specifying the conditions under which they can attain maximum usefulness.